Maternal complications and risk factors for mortality - Sulis Diana; Chatarina Umbul Wahyuni; Budi Prasetyo (SAGE Publishing, 2020)
Background: Maternal mortality could be prevented through early detection, including the period preceding pregnancy. Women of childbearing age are faced with extreme uncertainties, hence the purpose of this study was to analyse maternal complications and the possible high-risk factors connected to maternal mortality. Design and methods: A case-control study was used to study the causes of maternal mortalities amongst pregnant, delivering, and postpartum mothers between 2017 and 2018. A total sample size of 48 samples was selected through simple random sampling. Results: The result of logistic regression analysis showed nutritional status, prominence of anemia, history of illness, age, antenatal care ANC examination, method of delivery, late referral, occupational status, as well as postpartum complications, as the most influencing risk factors. This very high significance for maternal mortality was based on the chi-square value of 109.431 (p equal to 0.000), and R square (0.897). Conclusions: In conclusion, the potential risk factors of maternal mortality include nutritional status, state of anemia, history of illness, age, ANC examination, delivery method, late referral, occupational status, and pregnancy complications, which is specifically the most dominant factor.